The Role of Digital Education in Overcoming the Challenges Facing the Teaching of Islamic Culture, Perspective of Jordanian University Faculty Members - Al Dwairi , Awad Abdulraheem Awad (Journal of Ecohumanism, 2024)
This research investigates the problems encountered in teaching Islamic culture from the faculty members' point of view within faculties of Sharia law at Jordanian universities and determines the role of digital education in solving these problems. With a view to achieving these objectives, a questionnaire was designed containing 36 items and various fields related to the different challenges and the role of digital education with the descriptive analytical method. The research sample consisted of faculty members in the Sharia faculties of Yarmouk University, Al-Bayt University, and Mu'tah University. Results showed there were a lot of challenges that faced teaching Islamic culture, and how digital education is influential in surmounting them. These results support the null hypothesis of the study, that all faculty members face similar challenges in the implementation of digital education; therefore, no significant impact from demographic variables such as gender, department, or even years of experience. It means that other factors might be more conducive to surmounting the problems facing teaching Islamic culture, such as providing suitable technological infrastructure, technical and training support to faculty members, and the development of engaging and attractive digital educational materials compatible with the requirements of Islamic culture.